EKSPLORASI ETNOMATEMATIKA: PENGGUNAAN KONSEP GEOMETRI POLA DAN BENTUK PADA KLENTENG DEWI KWAN IM DAN TIE KONG PESAREAN GUNUNG KAWI - Maghfiroh, Khoridatul; Septia, Tika; Handayani, Ucik Fitri; Rahmawati, Tanti Diyah (Universitas PGRI Sumatera Barat, 2025)
This study explored the use of two-dimensional and three-dimensional geometric concepts in the patterns and shapes of the Klenteng Dewi Kwan Im and Tie Kong at Pesarean Gunung Kawi. This type of research is qualitative research with an ethnographic approach. The subjects in this study were the caretakers and administrators of Pesarean Gunung Kawi. The data collection techniques used in this study were observation, interview, and documentation. The results of this study indicate that the use of geometric concepts contained in the patterns and shapes of the Klenteng Dewi Kwan Im and Tie Kong buildings are Rectangle, Cube, Sphere, Quadrilateral Pyramid, Octagonal Prism, and Cylinder. The meaning contained in the patterns and shapes of the building has its meaning and philosophy according to the expectations based on the Chinese people's outlook on life.